KIF13A—A Key Regulator of Recycling Endosome Dynamics - Thankachan, Jerrin Mathew; Setty, Subba Rao Gangi (Frontiers in Cell and Developmental Biology, 2022)
Molecular motors of the kinesin superfamily (KIF) are a class of ATP-dependent motor proteins that transport cargo, including vesicles, along the tracks of the microtubule network. Around 45 KIF proteins have been described and are grouped into 14 subfamilies based on the sequence homology and domain organization. These motors facilitate a plethora of cellular functions such as vesicle transport, cell division and reorganization of the microtubule cytoskeleton. Current studies suggest that KIF13A, a kinesin-3 family member, associates with recycling endosomes and regulates their membrane dynamics (length and number). KIF13A has been implicated in several processes in many cell types, including cargo transport, recycling endosomal tubule biogenesis, cell polarity, migration and cytokinesis. Here we describe the recent advances in understanding the regulatory aspects of KIF13A motor in controlling the endosomal dynamics in addition to its structure, mechanism of its association to the membranes, regulators of motor activity, cell type-specific cargo/membrane transport, methods to measure its activity and its association with disease. Thus, this review article will provide our current understanding of the cell biological roles of KIF13A in regulating endosomal membrane remodeling.